Potential of Using Formalized Parameters for Modeling Speech Action - N. I. Stepykin (Научный диалог)
The quantitative parameters characterizing direct and indirect connections of words in the composition of the associative field “polite” are studied on the basis of the “Project of a multilingual associative thesaurus of politeness”. The aim of the study is to substantiate the potential of using formalized parameters when analyzing the stimulus-response ratio as a speech action. To achieve this goal, a free associative experiment, general scientific methods of analysis, synthesis and generalization were used. The functions of the index of direct and inverse associative strength, the number of mediations, the index of the associative power of mediation, the number of intersecting associates and the associative power of overlap are considered. The index of direct associative strength is used to calculate the probability of activation of a combination of stimulus — response, and the index of inverse associative strength reveals the degree of operationality of the corresponding combinations of response — stimulus. Analysis of the mediation parameter makes it possible to determine the number of potential signs, on the basis of which predication from stimulus to reaction is carried out. The index of the associative power of mediation characterizes the operationality of the ratio of stimulus - reaction, etc. The effectiveness of the use of formalized quantitative parameters in the modeling of speech action is proved.